ANALYSIS OF METHODS OF DETERMINATION OF BURNING MACHINES - Іващенко, Василь Трифонович; Лях, Михайло Михайлович; Журавльов, Дмитро Юрійович; Михайлів, Вадим Владислович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article analyses the basic methods for determining the usage of drilling wirelines during pulling-and-running operations while drilling and repairing oil and gas wells (descent and lifting of drilling tools, descent of the casings, descent and lifting of the pump-compressor pipes). The analytical dependencies of the determination of their usage on the basis of the number of bending cycles, the strength of the rope wire, the rope parts for the cycle of the downhill lifting of the drilling tool are discussed. The usage of ropes according to the criteria of their rotation is estimated which makes it possible to predict the durability of the rope.